Analisis Tingkat Literasi Kesehatan Anak Fase A Dan Hubungannya Dengan Partisipasi Dalam Pembelajaran Pendidikan Jasmani Sekolah Dasar Di Kota Makassar - Sufitriyono Sufitriyono; Ahmad Yani (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aims to analyze the relationship between health literacy levels and student participation levels in Physical Education (PJOK) learning for children in Phase. The study used a quantitative approach with a correlational method. The sample consisted of 80 elementary school students in Makassar city selected through a purposive sampling technique. The research instruments consisted of the Health Literacy for Young Children Questionnaire (HLYCQ) adapted version for Phase A and the Observation Sheet of Physical Education Participation (OS-PEP). Data were analyzed using descriptive statistics and Pearson correlation. The results of the analysis showed a strong positive and significant correlation between health literacy and student participation in PJOK learning (r = 0.612; p < 0.001), and health literacy explained approximately 37.4% of the variation in participation (R² = 0.374). Descriptively, the average health literacy score (mean = 78.35; SD = 10.21) and the Physical Education and Health (PJOK) participation score (mean = 15.87 out of a maximum of 20; SD = 2.41) indicate that the majority of Phase A students have a fairly good level of literacy and participation. This finding confirms that the greater a child's understanding of basic health, the greater their engagement in PJOK learning activities